Information technology performance measurement and improvement recommendation in Indonesian retail company - S W Perangin-angin; C H Primasari; Y P Wibisono (Universitas Ahmad Dahlan, 2021)
Information technology should work according to the needs and provide added value to the business. If the application of information technology does not provide added value to the business, information technology will only become a burden for the company. Therefore, it is necessary to measure performance to see to what extent the application of IT can support business processes and provide added value. This paper provides measurements and recommendations on IT governance in one of leading retail company in Indonesia. This research used descriptive quantitative research methods and IT Balanced Scorecard method that can provide an overview of IT performance in an organization based on four perspectives, such as Corporate Contribution, Customer Orientation, Operational Improvement, and Future Orientation. Based on the results of the analysis and measurement, the overall IT performance score was 62.64% where the score is in the â€œModerateâ€ category. The company contribution perspective got a score of 68.50%, the user orientation perspective was 63.00%, the operational improvement perspective was 62.06%, and the future orientation perspective was 57.44%. Several recommendations were constructed based on the consideration of the KPI value that must be improved. This can be a guide for other retail companies in formulating policies related to IT governance and enriching research in the field of IT performance measurement.